Employees’ Acceptance toward application of Industrialized Building System (IBS) in construction projects - Hamzah, Mohd Izwan; Kassim, Shamshul Anaz; Abd Ghani , Kay Dora; Hassan , Siti Hafizan (International Journal of Accounting, Finance and Business, 2025)
The Industrialized Building System (IBS) has evolved as an innovative technology in the building sector, providing increased efficiency, quality control, and environmental benefits. This study investigates the important elements influencing employee acceptance of IBS applications in construction projects. A survey was conducted among 150 industry professionals chosen using Krejcie and Morgan's (1970) sampling table. The data was evaluated using regression analysis to determine the impact of knowledge (EK), training and development (T&D), organizational support (OS), and IBS performance (IBSP) on employee acceptance. The study found that all four parameters have a substantial influence on IBS adoption (R² = 0.307), accounting for 30.7% of the variation. The findings highlight the relevance of structured training programs and organizational support in increasing employees' willingness to accept and adopt IBS in Malaysia's construction industry.